Enhancing Language Education in Uzbek Primary Schools: Integrating Polish Pedagogical Methods for Young Learners - Seytjanov Jetker; Erejepbaev Makhfirat (Miasto Przyszłości, 2024)
In the globalized world of the 21st century, proficiency in multiple languages is becoming increasingly essential. Recognizing this, educators in Uzbekistan are exploring innovative approaches to enhance language education, especially in primary schools. This scientific article proposes the integration of Polish pedagogical methods into the teaching of foreign languages to young students in Uzbek primary schools. Drawing on the rich tradition of Polish language education, we present recommendations to adapt and implement effective strategies for fostering language acquisition in a diverse and culturally rich context.